Implementasi Fatwa MUI No. 71/2023 dalam Program Dana Bergulir - Fany Nur Faridah; Indra Marzuki (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Revolving Fund Program aims to improve the community's economy through easy access to loans and has proven effective in increasing income. However, some people lack discipline in paying their obligations even though the government has provided payment facilities according to business conditions and financial capabilities. This study focuses on the practice of distributing zakat funds using the qardul hasan contract at Baznas Lebak, while also assessing its compliance with the Indonesian Ulema Council (MUI) Fatwa Number 71 of 2023. The research method used is qualitative with a case study approach through field research. A normative-empirical approach was chosen, namely examining the legal provisions in the MUI Fatwa normatively and analyzing its application empirically through observation and interviews. In this way, the study seeks to assess the extent to which the practice of zakat distribution in the form of revolving loans complies with sharia principles and the effectiveness of implementing the fatwa in improving community welfare.